Evaluation of Silk Fibroin-RGD-Stem Cell Factor Scaffold Effect on Adhesion, Migration, and Proliferation of Stem Cells of Apical Papilla - Jie Wei; Xiao-Qiang Sun; Ben-Xiang Hou (Hindawi Limited, 2021)
This study explored the effects of a silk fibroin-RGD-stem cell factor (SF-RGD-SCF) scaffold on the migration, proliferation, and attachment of stem cells of apical papilla (SCAPs). SF, SF-RGD, SF-SCF, and SF-RGD-SCF scaffolds were prepared, and laser confocal microscopy was used to observe the adhesion and growth status of SCAPs on the scaffolds. Furthermore, the numbers of SCAPs on the scaffolds were counted by a digestion counting method to evaluate their proliferation. Cells on the SF-RGD-SCF scaffold proliferated more than those on the other scaffolds and showed a more obvious tendency to migrate to the scaffold's deep porous structure after 7 d seeding. Live/dead cell staining results showed that almost all the adhered cells were alive after 7 d. Furthermore, cell counting showed that the number of cells on the SF-RGD-SCF scaffold was highest after both 1 and 7 d (P<0.05). Thus, the SF-RGD-SCF composite is biocompatible and promotes the migration, adhesion, and proliferation of SCAPs, making it of potential use as a scaffold for cell-homing pulp regeneration.